Environmental biochemistry of arsenic - Tamaki, S; Frankenberger, Jr, W T (Reviews of environmental contamination and toxicology, 1992)
Microorganisms are involved in the redistribution and global cycling of arsenic. Arsenic can accumulate and can be subject to various biotransformations including reduction, oxidation, and methylation. Bacterial methylation of inorganic arsenic is coupled to the methane biosynthetic pathway in methanogenic bacteria under anaerobic conditions and may be a mechanism for arsenic detoxification. The pathway proceeds by reduction of arsenate to arsenite followed by methylation to dimethylarsine. Fungi are also able to transform inorganic and organic arsenic compounds into volatile methylarsines. The pathway proceeds aerobically by arsenate reduction to arsenite followed by several methylation steps producing trimethylarsine. Volatile arsine gases are very toxic to mammals because they destroy red blood cells (LD50 in rats; 3.0 mg kg-1). Further studies are needed on dimethylarsine and trimethylarsine toxicity tests through inhalation of target animals. Marine algae transform arsenate into non-volatile methylated arsenic compounds (methanearsonic and dimethylarsinic acids) in seawater. This is considered to be a beneficial step not only to the primary producers, but also to the higher trophic levels, since non-volatile methylated arsenic is much less toxic to marine invertebrates. Freshwater algae like marine algae synthesize lipid-soluble arsenic compounds and do not produce volatile methylarsines. Aquatic plants also synthesize similar lipid-soluble arsenic compounds. In terrestrial plants, arsenate is preferentially taken up 3 to 4 times the rate of arsenite. In the presence of phosphate, arsenate uptake is inhibited while in the presence of arsenate, phosphate uptake is only slightly inhibited. There is a competitive interaction between arsenate and phosphate for the same uptake system in terrestrial plants. The mode of toxicity of arsenate is to partially block protein synthesis and interfere with protein phosphorylation but the presence of phosphate prevents this mode of action. There appears to be a higher affinity for phosphate than arsenate with a discriminate ratio of 4:1. It is estimated that as much as 210 x 10(5) kg of arsenic is lost to the atmosphere in the vapor state annually from the land surface. The continental vapor flux is about 8 times that of the continental dust flux indicating that the biogenic contribution may play a significant role in cycling of arsenic. It has not been established whether volatile arsenic can be released by plants. Further studies are needed to determine mass balances in the rate of transfer (fluxes) of arsenic in the environment.